2019
DOI: 10.1016/j.hal.2019.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomy and toxicity of Prorocentrum from Perhentian Islands (Malaysia), with a description of a non-toxigenic species Prorocentrum malayense sp. nov. (Dinophyceae)

Abstract: A B S T R A C TThirteen isolates of Prorocentrum species were established from the coral reefs of Perhentian Islands Marine Park, Malaysia and underwent morphological observations and molecular characterization. Six species were found: P. caipirignum, P. concavum, P. cf. emarginatum, P. lima, P. mexicanum and a new morphotype, herein designated as P. malayense sp. nov. Prorocentrum malayense, a species closely related to P. leve, P. cf. foraminosum, P. sp. aff. foraminossum, and P. concavum (Clade A sensu Chom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 70 publications
2
9
0
Order By: Relevance
“…Our field specimens and culture of P. concavum corresponded to the original description [39] of the species and further observations (e.g., References [13,14,19,39,40,41,42,43,44,45]) (see Supplementary Table S1, for details). Morton [41] described P. faustiae Morton, a species extremely similar to P. concavum , from reef flats near Heron Island, Great Barrier Reef, as broad oval cells 43–49 µm in length and 38–42 µm in width (synonymized with P. concavum by Chomérat et al [13]), while Mohammad-Noor et al [43] reported a range of 43–53 μM in length and 38–48 μM in width for P. concavum (but a larger range for specimens identified as P. cf.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Our field specimens and culture of P. concavum corresponded to the original description [39] of the species and further observations (e.g., References [13,14,19,39,40,41,42,43,44,45]) (see Supplementary Table S1, for details). Morton [41] described P. faustiae Morton, a species extremely similar to P. concavum , from reef flats near Heron Island, Great Barrier Reef, as broad oval cells 43–49 µm in length and 38–42 µm in width (synonymized with P. concavum by Chomérat et al [13]), while Mohammad-Noor et al [43] reported a range of 43–53 μM in length and 38–48 μM in width for P. concavum (but a larger range for specimens identified as P. cf.…”
Section: Discussionsupporting
confidence: 67%
“…Among them, species of the genus Prorocentrum C.G.Ehrenberg are recurrently reported from tropical and temperate waters, where they occur in benthic, epibenthic and planktonic habitats [5,12]. Approximately 70 species of Prorocentrum are known, with Prorocentrum micans C.G.Ehrenberg as the type, of which around 30 species are associated with sediments and live epiphytically on macroalgal surfaces, floating detritus and corals [5,12,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…emarginatum (MG600148, Lim et al . ), and a Brazilian strain UFBA033 of P. emarginatum (KY912158, Mendes et al . ) did not show detectable contents of DSTs nor pectenotoxin‐2 as determined by the instrumental analysis such as LC/MS/MS analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Two data sets with 13 species were assembled, one for the LSU locus with 68 sequences, and another for the ITS 1 www.CLCbio.com 2 www.ncbi.nlm.nih.gov/genbank/ locus with 72 sequences (Supplementary Table 1). Taxonomic sampling mainly followed Chomérat et al (2019), with the addition of recently described species in the genus (Luo et al, 2017;Nascimento et al, 2017;Lim et al, 2019). Each data set was analyzed with maximum likelihood and Bayesian inference approach under the same conditions as described below.…”
Section: Molecular Taxonomic and Phylogenetic Analysismentioning
confidence: 99%